An Empirical Study of In-App Purchase Intention Behavior of Generation Z in Mobile Games - Putratama, Donny; Retnowardhani, Astari (Journal of Information Systems Engineering and Business Intelligence, 2025)
Background: The rapid evolution of information technology has significantly transformed digital transactions and consumer behavior. Although in-game transactions and the mobile gaming industry are expected to experience significant growth, Generation Z gamers’ purchasing behavior remains underexplored.   Objective: This study aims to investigate the factors influencing Gen-Z’s intention to make in-app purchase of virtual goods within mobile games.   Methods: Partial Least Square (SmartPLS) analysis was conducted to examine whether live streamers, co-branding, good price, and mobile game loyalty affected in-app purchase intention among Gen-Z gamers.  Results: The results showed that live streamers, co-branding, and good price positively influenced gamers’ desire to purchase in-game items. Mobile game loyalty was also found to have the strongest influence on in-app purchase intention.  Conclusion: This study emphasized how game influencers, co-branding, fair pricing, and player loyalty influenced in-app purchase intentions among Indonesian Gen-Z mobile gamers. The findings revealed that using live streamers to showcase game characters, building stronger interactions with players, and offering sales promotions are effective ways to promote more in-app purchases.    Keywords: Co-Branding, Good Price, In-App Purchase Intention, Live Streamers, Mobile Game Loyalty.